Pengaruh Literasi Keuangan, Efikasi Diri Finansial, Dan Gaya Hidup Terhadap Perilaku Penggunaan Pinjaman Online Pada Mahasiswa Perguruan Tinggi di Pacitan - Sigit Dwi Santoso; Fadjar Harimurti; Sriyanto Sriyanto (Journal of Innovative and Creativity (Joecy), 2026)
The rapid growth of financial technology has increased the use of online loans among university students as a fast and easy alternative for financial needs. This study aims to analyze the influence of financial literacy, financial self-efficacy, and lifestyle on online loan usage behavior among university students in Pacitan. This research employs a quantitative approach with a causal method. Data were collected from 359 student respondents in Pacitan using a random sampling technique and a Likert scale questionnaire. Data analysis was performed using classical assumption tests and multiple linear regression analysis with SPSS. The results show that partially, financial literacy has a significant and positive effect on online loan usage behavior, indicating that better financial understanding leads to more prudent behavior. Financial self-efficacy has a significant and positive effect, suggesting that confidence in managing finances influences students' control and decisions regarding digital credit. Lifestyle also has a significant and positive effect, where a higher lifestyle increases the intensity of online loan usage. Simultaneously, all three variables significantly influence online loan usage behavior with an Adjusted R Square value of 0.335, meaning these independent variables explain 33.5% of the variation in student behavior, while the remaining 66.5% is influenced by other factors outside the model.